2002
DOI: 10.1074/jbc.m109057200
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-dependent Human Vascular Smooth Muscle Cell Adhesion Requires Selective Vitronectin Phosphorylation by Ectoprotein Kinase CK2

Abstract: Urokinase (uPA)-and urokinase receptor (uPAR)-dependent cell adhesion to the extracellular matrix protein vitronectin (Vn) is an important event in wound healing, tissue remodeling, immune response, and cancer. We recently demonstrated that in human vascular smooth muscle cells (VSMC) uPA/uPAR are functionally associated with the ectoprotein kinase casein kinase-2 (CK2). We now asked whether CK2 regulates uPA-dependent cell adhesion to Vn, since the latter is a natural CK2 substrate. We found that Vn is indeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Several extracellular proteins have been identified as substrates of the CK2 ectokinase activity. Vitronectin has been shown to be phosphorylated extracellularly by CK2, and evidence has been presented to demonstrate that its phosphorylation regulates the adhesion of cells to the extracellular matrix (2,3). More recently, it has been shown that CK2 phosphorylates the C9 complement and it has been suggested that this phosphorylation might control cell lysis caused by this complement protein (4).…”
mentioning
confidence: 99%
“…Several extracellular proteins have been identified as substrates of the CK2 ectokinase activity. Vitronectin has been shown to be phosphorylated extracellularly by CK2, and evidence has been presented to demonstrate that its phosphorylation regulates the adhesion of cells to the extracellular matrix (2,3). More recently, it has been shown that CK2 phosphorylates the C9 complement and it has been suggested that this phosphorylation might control cell lysis caused by this complement protein (4).…”
mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that this CK2-like ectokinase enzyme phosphorylates a number of external proteins or the extracellular domains of membrane proteins (5)(6)(7)(8). However, there is a dearth of evidence concerning the mechanisms through which the CK2-like enzyme or other ectokinases are exported and about the structural features that tag these proteins for export.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there are several reports that an ectokinase has the characteristics of protein kinase casein kinase 2 (CK2) (2)(3)(4). A CK2-like ectokinase activity has been reported to be responsible for the phosphorylation of vitronectin, an extracellular matrix protein (5,6), and of the external domain of the ␤-amyloid precursor protein (7) and T lymphocyte surface proteins (8). However, there is no information about the structural features that are responsible for the export of CK2 or other ectokinases.…”
mentioning
confidence: 99%
“…Threonine 50 and 57 of vitronectin can be phosphorylated by CK2 [31] and the phosphorylation enhances its binding to both alpha(v)beta3 integrin [64] and urokinase receptor [65]. Furthermore, the serine 378 of vitronectin is phosphorylated by PKA, which induces a conformational change and enhances the phosphorylation by CK2 [66].…”
Section: Vitronectinmentioning
confidence: 99%